FAKTORFAKTOR YANG BERHUBUNGAN DENGAN BEBAN KERJA PERAWAT DI INSTALASI RAWAT INAP BLUD RSU DR. M.M. DUNDA LIMBOTO KABUPATEN GORONTALO - Buheli, Kartin (Sainstek, 2011)
Hospitals as health care facilities play an important role in realizing the degree of public health, individual and holding of a comprehensive health service. In macro optimizing health services in hospitals were not fully implemented due to, among other medical personnel and equipment utilization are not yet sufficient. Conditions and situations of Totoś hospitals that have backgrounds exclusive hospital has less support in providing excellent service should be developed along with the high demands of the public / patient and patientś complaints of dissatisfaction with services provided Toto hospital either received orally or through the media mass. This study aimed to determine the factors associated with inpatient satisfaction in hospitals Toto based on effectiveness, comfort, information, human relations, and timeliness. Type of research is quantitative research design \